A Comparison Between Schlumberger and Wenner Configurations in Delineating Subsurface Water Bearing Zones: A Case Study of Rawalakot Azad Jammu and Kashmir, Pakistan - Abrar Niaz; Arbab Manzoor wan,; Tehmina Bibi; Javed Akhter Qureshi; Sabit Rahim; Fahad Hameed; Arshad Ali Shedayi (International Journal of Economic and Environment Geology, 2021)
The Schlumberger and Wenner Electrical Resistivity Survey techniques have been used in comparison for the determination of groundwater potential in District Rawalakot, Azad Jammu and Kashmir. The terameter SAS4000 with accessories was used for data acquisition. The data were processed by employing IPI2WIN software to determine the depth, thickness and true resistivity of the subsurface layers. The present study indicated the subsurface depth coverage of Schlumberger configuration is greater than Wenner configuration. The apparent resistivity maps using both Wenner and Schlumberger techniques at the same locations have been prepared at 3m, 4m, 9m, 10m, 27m, 30m, 50m, 51m, 100m, and 150m depths respectively for groundwater assessment. The differences in resistivity contour closures, in both types of maps, arise due to lateral variations of subsurface lithology. Longitudinal conductance, transverse resistance and anisotropic maps were also prepared. The different contour closures in the Wenner map were due to mixed lithology of alluvium with variable water contents. The subsurface geology i.e. clay, sandstone boulder clay, and dry sandy soil were interpreted which are in close agreement with the surface geology of the area. The aquifers of the project area are designated as confined and unconfined good water potential indicated by low values of resistivity. The water-bearing strata consist of sand, gravel, boulder clay and sandy clay.